MSMEs Sales Information System by Papuan Children’s in Nabire - Penison Wenda; Eko Sediyono (International Journal of Information Technology and Business, 2023)
Offline and online business developments continue to develop in the midst of the covid-19 outbreak that continues to hit, some are unable to adapt so that their business goes bankrupt and some are able to survive and also grow, for that the MSMEs (Micro Small and Medium Enterprises) sales information system of Karya Anak Papua must be able to understand the existing situation because technological developments continue to develop in every business sector. This situation has an impact on the local community, especially the local Papuan community, who with improvised conditions and minimal business strategies try to survive in any way so that their daily needs can be met, some have started to pick up technology by starting to market their work online, but some have also started to pick up technology by starting to market their work online. which have not been. The role of MSMEs (Micro Small and Medium Enterprises) for the country's economy is very important and strategic. This is supported by data on MSMEs (Micro Small and Medium Enterprises) macroeconomic indicators which are quite dominant in the Indonesian economy. In accordance with the economic development of the regions in Indonesia, there are many obstacles faced by the local government in developing MSMEs originating from internal and external. the best policy in developing MSMEs. This study wants to examine the development of MSMEs (Micro Small and Medium Enterprises) leading commodities in Nabire Regency.